Report on professional attachment with Inland Revenue Authority of Singapore. - Chen, Jacqueline Lujun. (2009)
The purpose of this report is to summarize on my professional attachment experience with Inland Revenue Authority of Singapore (IRAS). I was posted to the Contact Centre as a call officer to handle queries relating to individual income tax matters. IRAS has an excellent working environment where colleagues are friendly and always ready to help. This has enhanced my experience in IRAS and made me learnt a lot of things, mainly tax knowledge, communication skill, interpersonal skill and the fact that it is important to exercise our judgment when working.